The underlying mechanism of nuclear and mitochondrial DNA damages in triggering cancer incidences: Insights into proteomic and genomic sciences - Saadi, Sami; Nacer, Nor Elhouda; Saari, Nazamid; Mohammed, Abdulkarim Sabo; Anwar, Farooq (Elsevier, 2024)
The attempt of this review article is to determine the impact of nuclear and mitochondrial damages on the propagation of cancer incidences. This review has advanced our understanding to altered genes and their relevant cancerous proteins. The progressive raising effects of free reactive oxygen species ROS and toxicogenic compounds contributed to significant mutation in nuclear and mitochondrial DNA where the incidence of gastric cancer is found to be linked with down regulation of some relevant genes and mutation in some important cellular proteins such as AMP-18 and CA-11. Thereby, the resulting changes in gene mutations induced the apparition of newly polymorphisms eventually leading to unusual cellular expression to mutant proteins. Reduction of these apoptotic growth factors and nuclear damages is increasingly accepted by cell reactivation effect, enhanced cellular signaling and DNA repairs. Acetylation, glycation, pegylation and phosphorylation are among the molecular techniques used in DNA repair for rectifying mutation incidences. In addition, the molecular labeling based fluorescent materials are currently used along with the bioconjugating of signal molecules in targeting disease translocation site, particularly cancers and tumors. These strategies would help in determining relevant compounds capable in overcoming problems of down regulating genes responsible for repair mechanisms. These issues of course need interplay of both proteomic and genomic studies often in combination of molecular engineering to cible the exact expressed gene relevant to these cancerous proteins.